Watershed development projects in India: an evaluation - Kerr, John M. (International Food Policy Research Institute, 2002)
The Green Revolution that transformed agriculture elsewhere in India had little impact on rainfed agriculture in the semi-arid tropical regions, where agricultural productivity is low, natural resources are degraded, and the people are poor. In the 1980s and 1990s, agricultural scientists and planners aimed to promote rainfed agriculture through watershed development. A watershed is an area from which all water drains to a common point, making it an attractive unit for technical efforts to manage water and soil resources for production and conservation. Watershed management is complicated, however, by the fact that watersheds rarely correspond to human-defined boundaries. Also, watershed projects often distribute costs and benefits unevenly, with costs incurred disproportionately upstream, typically among the poorer residents, and benefits realized disproportionately downstream, where irrigation is concentrated and the wealthiest farmers own most of the land.